Chinese Globalization : a Profile of People-Based Global Connections in China. - Sun, Jiaming (Routledge contemporary China series., 2013)
This book examines the explicit effects of global connectivity on local culture and society in post-reform mainland China. It focuses on individual level globalization in China and how global socialization impacts local residents' behaviors, lifestyle, value orientation and the consequence of local transformation. Asking questions such as: What types of individual global connections have emerged and developed in China over the last three decades?What aspects of local transformations are influenced by such global connections?How does the impact of global connect.